Analysis of the situation room in a FHU: a view of women's health careAnalysis of the situation room in a FHU: a view of women's health care - Marilia Gabriela da Rocha Vital; Nara Lins; Katharine Menezes; Jeanne Cunha; Thereza Neves; Bruno ishigami (Universidade de Santa Cruz do Sul, 2012)
Rationale and Objectives: Among the Brazilian health care programs, there is the Program for Integral Attention to Women's Health (PAISM), which offers full assistance to the female population in accordance with the principles and guidelines of SUS within primary care policy. This study aimed to analyze the monthly monitoring in 2009 and 2010 through epidemiological indicators of the situation room regarding women's health in a Family Health Unit (FHU) of Recife-PE. Methods: This is a descriptive epidemiological, comparative and exploratory study carried out in a FHU of the Health District V, located in Recife-PE and called Planet of the Apes II, a member of PET-Health. A total of eight indicators were assessed, representing 100% of the data in spreadsheets presented in the Situation Room in the abovementioned years. Results: The assessed Family Health Unit, in general, reached the goals established by the Ministry of Health regarding PAISM in the analyzed indicators for prenatal care and collection of cytopathologic specimens for uterine cancer surveillance. Conclusion: The FHU must always be instructed and trained to provide comprehensive care to women's health, a perspective that includes health promotion, control of the most prevalent diseases in this group and ensuring the right to health. However, it is worth emphasizing that the results shown here cannot be interpreted alone, or be the only source of information and evaluation of care. KEYWORDS: Women's Health. Primary Health Care. Health Policies